2023
DOI: 10.1038/s41563-023-01497-1
|View full text |Cite
|
Sign up to set email alerts
|

Puddle formation and persistent gaps across the non-mean-field breakdown of superconductivity in overdoped (Pb,Bi)2Sr2CuO6+δ

Abstract: The cuprate high-temperature superconductors exhibit many unexplained electronic phases, but the superconductivity at high doping is often believed to be governed by conventional mean-field Bardeen–Cooper–Schrieffer theory1. However, it was shown that the superfluid density vanishes when the transition temperature goes to zero2,3, in contradiction to expectations from Bardeen–Cooper–Schrieffer theory. Our scanning tunnelling spectroscopy measurements in the overdoped regime of the (Pb,Bi)2Sr2CuO6+δ high-temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Besides, we have directly counted the percentage of normal regions in the OD-15K sample and found that it is merely ~10% (Supplementary Material Section IX ); thus is not enough to account for the strong arc-like zero-bias QPI. This is consistent with the finding of a 12% gapless region in similar overdoped Bi-2201 with T c = 12 K in another STM work using a different data analysis method 7 . The normal-carrier QPI features start to appear in the slightly overdoped OD-28K sample, where strongly overdoped normal regions are very scarce, also indicating that the normal carrier QPI is not caused by real-space phase separation.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Besides, we have directly counted the percentage of normal regions in the OD-15K sample and found that it is merely ~10% (Supplementary Material Section IX ); thus is not enough to account for the strong arc-like zero-bias QPI. This is consistent with the finding of a 12% gapless region in similar overdoped Bi-2201 with T c = 12 K in another STM work using a different data analysis method 7 . The normal-carrier QPI features start to appear in the slightly overdoped OD-28K sample, where strongly overdoped normal regions are very scarce, also indicating that the normal carrier QPI is not caused by real-space phase separation.…”
Section: Resultssupporting
confidence: 93%
“…In the overdoped regime, the mechanism for the disappearance of superconductivity at the quantum superconductor to metal transition (QSMT) is still elusive 3 . It was usually considered to be due to the closing of superconducting gap like in conventional superconductors, but there are growing evidence that the gradual losing of phase coherence plays a crucial role in the QSMT 4 7 . Especially, mutual inductance experiment reveals that overdoped cuprates exhibit an anomalous missing of superfluid density 4 , 5 , 8 , which is intimately related to the decrease of T c .…”
Section: Introductionmentioning
confidence: 99%
“…From [80], using scanning tunneling spectroscopy, the puddles are observed to be present in the overdoped regime of (Pb, Bi) 2 Sr 2 CuO 6+δ and as the authors point out, the breakdown of superconductivity is not the consequence of a vanishing pairing interaction and does not follow the Bogoliubov-de Gennes description. From the perspective of the present work, this might be represented by the finite CM momentum of the Cooper pairs.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…[4] One prominent issue arises as to whether there is normal fluid in the superconducting state due to the missing charge carriers if fewer and fewer carriers are condensed into the superconducting state in the overdoped region. [5] In Bi 2 Sr 2 CuO 6+δ (Bi2201) superconductors, normal electrons are observed in the superconducting state by scanning tunneling microscopy (STM) both in the real space [6] and in the reciprocal space [7] which are strongly affected by disorder. Whether it is universal that the normal fluid always exists in the superconducting state in the overdoped samples remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%